Longshore current profiles with wave-current interaction - Soe Myint; Sutat Weesakul; Suphat Vongvisessomjai; Tanaka, Hitoshi; Finist Government (Bangkok : Asian Institute of Technology, 1993)
The steady state profile of the longshore current induced by regular, breaking, over a parallel bottom contours of plane and barred beach was studied theoretically and experimentally. A conventional momentum approach was adopted to formulate the governing equation. Wave-current interaction was also induced in the wave propagation model and snell law. The model incorporate new expression for the current effect on longshore velocity profile by using Tanaka's (1992) bottom friction factor of combined wave and current. Numerical approach was used to solve all governing equation. The predicted current profiles were compared with the laboratory experiments of Visser (1991) for plane beach and with the present experiment on barred beach. In order to find the velocity profiles of a barred beach, the experimental measurements were performed in a basin with a pump recirculation through openings in the wave guides. Detailed experimental results were presented for different wave fields for a beach slope and a beach roughness. However the uniformity of the longshore currentwas not well satisfied. Moremodification ofcirculation system was recommended. The computed longshore current profile using wave-current interaction was slightly different from that of no interaction. However for the interaction model the advantage of the input parameter ks was to reflect the physical condition of bed roughness instead of bed coefficient C in bottom shear stress formula. The different lateral mixing formulae was tested and it was found that the slightly change of velocity profile after the peak point and outside the surf zone. For overview the effect was small. Forbarbreak, the secondbreakingpointwas foundin laboratory. Itcould also be simulated in numerical model with different parameter in wave decay model. The two peaks of the velocity profile could be computed and compare with laboratory data. The peak ofthe current velocity profile shifting was also found.
Thesis (M.Eng.) - Asian Institute of Technology, 1993
A thesis submitted in partial fulfilment of the requirement for the degree of Master of Engineering.
Keywords: Waves; Coastal engineering